First female record of the Psychidae species Dahlica michaela Arnscheid, 2016, in the Pyrenees of Huesca in Aragon (Spain) (Lepidoptera: Psychidae, Naryciinae) - W. A. Arnscheid; M. R. Gärtner (SHILAP, 2018)
In 2016 the senior author described the Psychidae species Dahlica michaela from the Pyrenees of Aragon based on 10 males, reared from larvae. No females were included in the type series. It was assumed that the female larvae live hidden on the ground near rocks where the male larvae were found. During a hiking trip on 28 April 2017 a small larval case has been detected attached near the base of a rock at the type locality. From this case a female emerged on 10 May 2017.